IMPROVING STUDENTS’ WRITING SKILL BY USING SCAFFOLDING TECHNIQUE TO THE SEVENTH GRADERS OF SMP BOPKRI GODEAN - Rika Rimawati; Hermayawati Hermayawati (Journal of English Language Teaching and English Linguistics, 2017)
The background of the study was based on the phenomenon at the seventh graders of the SMP BOPRI Godean. Learning English especially writing skill were still low in mastering vocabulary, sentence structure, and paragraph organizing. The research aimed (1) to analyze the students’ writing by using scaffolding technique; (2) to describe the improvement of the students’ writing skill by using scaffolding technique; and (3) to find out the students’ interests in writing skill by using scaffolding technique. To solve the problem, the researcher conducted Classroom Action Research and applied scaffolding technique in teaching English to improve student’s ability in writing skill. The participants of this research were the 14 students of the seventh graders of SMP BOPKRI Godean. In this study, the researcher conducted a scaffolding technique of teaching writing descriptive text in three cycles by using scaffolding model adapted from Silvia Read. The five steps in scaffolding technique by Silvia Read were inquiry, modeling, shared, collaborative, and independent. The researcherexpected that the students could improve their writing skill by using the scaffolding technique and interested in English writing skill. The result of this study was showed by pre-test and post-test. In pre-test, the students’ average score was 49, whereas in the students’ post-test cycle one, the students’ average score was 64. In the second cycle, the students’ average score was 75.9. Finally, the researcher could conclude that the result of this research showed an improvement of the students’ writing skills by using scaffolding technique.